Prevalence of pain and quality of life in high-performance athletes - Martins, L.; Paiva, J.; Freitas, A.; Miguel, L.; Andrade, A.; Neto, F.; Bacha, A.; Dalenogare, L.; Menezes, W. V.; Silva, A.; Bolze, M. A.; Maia, F. (British Journal of Sports Medicine, 2014)
Background: On study of athletes, science has been devoted focusing on athletic performance. However, more recently, researchers have been concerned with other aspects that transcend obtaining results such as the health and well being of high-performance athletes. Objective: To investigate the occurrence of pain and associated factors and its relation to the quality of life in elite athletes of various sports. Design: An observational, cross-sectional and analytical study. Setting: Level of competition: International, World and Olympic. Participants: The study population was composed of 86 high-performance athletes: 13 of judo, 42 of swimming, 22 of parachuting, and 9 of volleyball. Risk factor assessment: The risk factors were: training aspects (sports practice time in years, number of training hours accumulated per week) and complementary training (stretching, resistance exercises and functional training). The evaluation was made by self-reported questionnaires. The occurrence of pain was assessed as a risk factor for quality of life. Main outcome measurements: The prevalence of pain (primary outcome) was estimated by self-reported questionnaire referring to anatomical region that occurred. Quality of life (secondary outcome) was investigated using the WHOQOL-Brief. Results: Sports practice time and gender were not associated with the occurrence of pain. Multiple logistic regression analysis showed that sport and age were associated with the outcome (P<.05). Pain was associated with lower quality of life in domains physical, psychological and environmental Prevalence of pain according to sport. Conclusions: The occurrence of pain can affect the amount of training supported by the athlete, resulting in decreased performance. Therefore it is imperative the monitoring for reducing pain in elite athletes. These are highly demanded both psychologically and physically; that's why it is equally important that they also be assisted to improve their perceived quality of life.